PERANCANGAN APLIKASI PEMBELAJARAN BENCANA TSUNAMI DI INDONESIA BERBASIS WEB - Samuel Kurniawan (Fakultas Teknologi Informasi Universitas Tarumanagara, 2023)
The Web-Based Design of a Tsunami Disaster Monitoring Application in Indonesia aims to make it easier for users to obtain information related to Tsunami Disasters in every province in Indonesia. This application aims to provide information ranging from total cases, active cases, dead victims, survivors, missing victims and information related to the Tsunami in Indonesia. Users can see data visualization in the form of a map of Tsunami cases and the total number of survivors in Indonesia. The design of this application uses the Waterfall model System Development Life Cycle (SDLC) development methodology. The database used in this application is MySQL. Mapping in this application uses the Leaflet system which can display data and map visualization of Indonesia. The programming languages used are HTML and PHP. The test results show that this application can be understood and used to find information from the Tsunami Disaster in Indonesia.